Diverse scenarios of syntactic complexity - Alvarez González, Albert; Estrada Fernández, Zarina; Chamoreau, Claudine (Typological studies in language,, 2019)
"This volume surveys the phenomenon of syntactic complexity in a diversity of languages and from a diversity of theoretical perspectives. The topics include clause combining strategies such as relative, complement, and adverbial clauses, serialization, clausal nominalizations, but also the switch reference systems involved in clause chains, the role of insubordination and the influence of language contact in the development of syntactic complexity as well as the acquisition of complex clauses in child language and the grammaticalization processes leading to syntactic complexity. These studies illustrate the varied aspects involved in clause combining and help to understanding how syntactic complexity works and evolves in the world's languages, how it varies across languages, how it is influenced by language contact, how it is acquired. As such, this book gives the opportunity for readers to expand both their typological and their theoretical knowledge about syntactic complexity in a variety of languages" --